Effects of dioxins on animal spermatogenesis: A state-of-the-art review - Faiad, Walaa; Soukkarieh, Chadi; Murphy, Denis J.; Hanano, Abdulsamie (Frontiers in Reproductive Health, 2022)
The male reproductive system is especially affected by dioxins, a group of persistent environmental pollutants, resulting in irreversible abnormalities including effects on sexual function and fertility in adult males and possibly on the development of male offspring. The reproductive toxicity caused by dioxins is mostly mediated by an aryl hydrocarbon receptor (AhR). In animals, spermatogenesis is a highly sensitive and dynamic process that includes proliferation and maturation of germ cells. Spermatogenesis is subject to multiple endogenous and exogenous regulatory factors, including a wide range of environmental toxicants such as dioxins. This review discusses the toxicological effects of dioxins on spermatogenesis and their relevance to male infertility. After a detailed categorization of the environmental contaminants affecting the spermatogenesis, the exposure pathways and bioavailability of dioxins in animals was briefly reviewed. The effects of dioxins on spermatogenesis are then outlined in detail. The endocrine-disrupting effects of dioxins in animals and humans are discussed with a particular focus on their effects on the expression of spermatogenesis-related genes. Finally, the impacts of dioxins on the ratio of X and Y chromosomes, the status of serum sex hormones, the quality and fertility of sperm, and the transgenerational effects of dioxins on male reproduction are reviewed.